Strategi Pemasaran, Skema Laporan Keuangan, dan Perlakuan Pajak bagi UMKM Rumah Bakso di Tangerang Selatan - Damayanti, Melsanda; Wardokhi, Wardokhi; Khotimah, Husnul (Jurnal Pajak Populis, 2025)
ABSTRACT This Community Service Program (PKM) aims to enhance the capacity of MSME (Micro, Small and Medium Enterprises) actors, particularly Rumah Bakso in Pamulang Barat, in terms of marketing strategy, financial reporting in accordance with SAK EMKM, and tax compliance based on Government Regulation No. 23 of 2018. The program activities involved socialization, interactive discussions, and technical mentoring. Results showed significant improvements in participants' understanding of innovative marketing strategies (e.g., food trucks), the importance of financial record-keeping, and the calculation and reporting mechanisms of Final Income Tax. This initiative is expected to support business sustainability and tax compliance among MSMEs.